Remittance Status and Contribution to GDP of Nepal - Ojha, Krishna Prasad (NCC Journal, 2019)
The research paper aims to analyze the status of remittance and its contribution to GDP of Nepal. The study has adopted the descriptive and analytical research design. The study is quantitative in nature. Most of the developing countries like Nepal depend on remittance as the major source of foreign currency earning. Remittance plays an important role in economic development of a country. Nepal has also long history of international labor migration about 200 years ago Nepali migrant laborers are contributing substantial amount as remittance inflows through legal channel which has positive impact on GDP, per-capita income, Capital formation, education etc. The volume of remittance is much more than the records because, migrants are using illegal ways due to ignorance and difficulty in receiving amount from legal ways.